Phlebotomine Sand Fly Fauna and Leishmania Infection in the Vicinity of the Serra do Cipó National Park, a Natural Brazilian Heritage Site. (22nd February 2015) - Lana, Rosana Silva; Michalsky, Érika Monteiro; Fortes-Dias, Consuelo Latorre; França-Silva, João Carlos; Lara-Silva, Fabiana de Oliveira; Lima, Ana Cristina Vianna Mariano da Rocha; Moreira de Avelar, Daniel; Martins, Juliana Cristina Dias; Dias, Edelberto Santos
Abstract : In the New World, the leishmaniases are primarily transmitted to humans through the bites of Leishmania -infected Lutzomyia (Diptera: Psychodidae) phlebotomine sand flies. Any or both of two basic clinical forms of these diseases are endemic to several cities in Brazil—the American cutaneous leishmaniasis (ACL) and the American visceral leishmaniasis (AVL). The present study was conducted in the urban area of a small-sized Brazilian municipality (Jaboticatubas), in which three cases of AVL and nine of ACL have been reported in the last five years. Jaboticatubas is an important tourism hub, as it includes a major part of the Serra do Cipó National Park. Currently, no local data is available on the entomological fauna or circulating Leishmania . During the one-year period of this study, we captured 3, 104 phlebotomine sand flies belonging to sixteen Lutzomyia species. In addition to identifying incriminated or suspected vectors of ACL with DNA of the etiological agent of AVL and vice versa, we also detected Leishmania DNA in unexpected Lutzomyia species. The expressive presence of vectors and natural Leishmania infection indicates favorable conditions for the spreading of leishmaniases in the vicinity of the Serra do Cipó National Park.